Pengaruh Multikultural Leadership, Kompetensi Multikultural Guru, Kompetensi Multikultural Siswa, Terhadap Kinerja Akademik Siswa se SMA Muara Jambi - Aprillitzavivayarti, Aprillitzavivayarti; Hendri, Hendri (Educational Leadership and Management Journal, 2023)
The purpose of this study is to evaluate how multicultural leadership, teachers' multicultural competence, and students' multicultural competence affect the academic performance of students in Muara Jambi high schools. This research uses quantitative methods and uses a questionnaire as an instrument to collect data from students in Muara Jambi high schools. The Structural Equation Modeling Partial Least Square (SEM PLS) method was used to analyze and evaluate the cause-and-effect relationship between independent variables and dependent variables. The research sample consisted of 192 student respondents from Muara Jambi High School. The four variables studied in this study are multicultural leadership, teacher multicultural competence, student multicultural competence, and student academic performance. The results showed that there was a significant influence of multicultural leadership, teachers' multicultural competence, and students' multicultural competence on students' academic performance. And for the results of the p-values themselves, namely H1 the effect of multicultural leadership on student academic performance has a value of 0.007 from this value, hypothesis one is influential or supported. For H2, the effect of multicultural competence of teachers on student academic performance has a value of 0.000 from this value, this second hypothesis is influential or supported. And finally H3 the effect of students' multicultural competence on students' academic performance has a value of 0.000 from this value this third hypothesis is influential or supported. Therefore, in this study, all variables greatly affect the academic performance of students at Muara Jambi High School.